Pengaruh Perbandingan Jamur Tiram Dan Sotong Pada Pembuatan Nugget Terhadap Kualitas Fisik Dan Daya Terima Konsumen - Saputra, Muhammad Dani; Sachriani, Sachriani; Ngurah S, I Gusti Ayu (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine and analyze the effect of the comparison of oyster mushrooms and cuttlefish in making nuggets on physical quality and consumer acceptability including aspects of color, aroma, taste and texture. The research will take place from September 2022 to January 2024 at Jakarta State University. This research is included in quantitative research with experimental methods on 3 comparative treatments (90% oyster mushrooms with 10% cuttlefish, 80% oyster mushrooms with 20% cuttlefish and 70% oyster mushrooms with 30% cuttlefish). The sampling technique is carried out randomly (random sampling), namely by giving a number or code to each sample, where the code is only known by the researcher. Testing with organoleptic tests, namely hedonic tests carried out on 30 somewhat trained panelists. The results of the hypothesis test showed that a comparison of 70% oyster mushrooms with 30% cuttlefish obtained the highest score for tenderness and oil absorption capacity. The results of statistical hypothesis testing using the Friedman test show that there is an influence of the comparison of oyster mushrooms and cuttlefish in making nuggets on consumer acceptance. The results of this research are that nugget products with a ratio of 80% oyster mushrooms and 20% cuttlefish are considered successful and accepted by consumers because they get a good assessment and are recommended for development and marketing